2022
DOI: 10.1002/pat.5716
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dglucitolbased Gemini amphiphilic nanotransporters

Abstract: A newer class of Gemini amphiphiles was prepared using D-glucitol as a template. C 18 alkyl chains are incorporated on the template to confer hydrophobicity while monomethoxy polyethylene glycol (mPEG) moiety of varied size imparts hydrophilicity. An acetonide group mounted on glucitol moiety is used to maintain rigidity in the amphiphilic architecture and to study its impact on aggregation and transport ability.The aggregation behavior of the synthesized amphiphiles was studied through fluorescence spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Ester groups are a prominent example for cleavable linkers, which can be induced via low pH values or esterases (Figure 16). [171] Disulfide bonds are linkers that can be cleaved by reducing agents, like glutathione which is also found in cells, thus enabling a redoxtriggered micelle degradation and release of encapsulated drugs (Figure 16). [147b] Other disulfide detergents reported by Xue et al revealed good extraction yields and efficient stabilization of membrane proteins comparable to commercially available detergents.…”
Section: Stimuli-responsive Linkersmentioning
confidence: 99%
“…Ester groups are a prominent example for cleavable linkers, which can be induced via low pH values or esterases (Figure 16). [171] Disulfide bonds are linkers that can be cleaved by reducing agents, like glutathione which is also found in cells, thus enabling a redoxtriggered micelle degradation and release of encapsulated drugs (Figure 16). [147b] Other disulfide detergents reported by Xue et al revealed good extraction yields and efficient stabilization of membrane proteins comparable to commercially available detergents.…”
Section: Stimuli-responsive Linkersmentioning
confidence: 99%
“…29 As per the earlier optimized procedure of our group, 0.12 mg of the dye in 5 mg/mL of the nanocarrier solution was prepared for encapsulation as a stock solution. T A B L E 2 Transport efficiency, transport capacity, and encapsulation efficiency of nanocarriers (13,16,17,18) for Nile red, nimodipine, and curcumin. cerebral blood flow by flowing intra-arterial, intravenous, or oral administration in humans as well as in animals.…”
Section: Nile Red Encapsulationmentioning
confidence: 99%
“…Two series of nonionic double chain amphiphiles (mPEG-750 and mPEG-1000) were synthesized (13)(14)(15)(16)(17)(18) by varying the alkyl (C 8 /C 20 ) and perfluoroalkyl (C f8 ) moiety. Except 14 and 15 all other amphiphilic systems of both series were found to be soluble in water and form nanosized aggregates as established by DLS study.…”
Section: Physicochemical Characterization and Study Of Self-aggregati...mentioning
confidence: 99%
See 2 more Smart Citations